Gut and lung microbiome profiles in pregnant mice - Wiscovitch-Russo, Rosana; Taal, Aji Mary; Kuelbs, Claire; Oldfield, Lauren M.; Ramar, MohanKumar; Singh, Harinder; Fedulov, Alexey V.; Gonzalez-Juarbe, Norberto (Frontiers in Microbiology, 2022)
In recent years, microbiome research has expanded from the gastrointestinal tract to other host sites previously thought to be abacterial such as the lungs. Yet, the effects of pregnancy in the lung and gut microbiome remains unclear. Here we examined the changes in the gut and lung microbiome in mice at 14 days of gestation. Lung tissue and stool samples were collected from pregnant and non-pregnant female BALB/c mice, DNA was isolated, amplified, and bacterial specific V4 16S rRNA gene was sequenced. Using an in-house bioinformatic pipeline we assessed the microbial composition of each organ using stool and lung tissue samples. The stool data showed that Lachnospiraceae and Lactobacillaceae were more abundant in the pregnant mice. Likewise, Lactobacillaceae were dominant in the lungs of pregnant mice. However, Streptococcaceae were dominant in the lungs of non-pregnant mice with a low microbial abundance in the pregnant mice. A permutation test showed that pregnancy significantly contributes to the variance in both the lung and stool microbiome. At the same time, we estimate that 49% of the total detected operational taxonomic units were shared between the stool and lung data. After removing common stool-associated bacteria from the lung dataset, no microbial differential abundance was detected between the pregnant and non-pregnant lung microbial community. Thus, pregnancy contributes to variance to the lung and stool microbiome but not in the unique lung microbiota.